Numerical simulation of the energy distribution into the spark at the direct detonation initiation - Korytchenko, K.V.; Golota, V.I.; Kudin, D.V.; Sakun, O.V. (Вопросы атомной науки и техники, 2015)
A numerical model of the direct initiation of the detonation in gases exposed to the action of the spark discharge taking into consideration the retarded vibrational excitation of molecules behind the shock wave front has been developed. The calculations showed that the critical time of the energy input into the spark discharge is equal to the separation time of the shock wave from the current - conductive channel of the spark. The model allows for the prediction of the availability or unavailability of a direct initiation depending on the parameters of electrical discharge circuit.